Radiosurgery: Teenage Sex or Midlife Crisis? - Tripathi, Manjul (Frontiers in Surgery, 2022)
Martin Luther King, in his famous speech, mentioned that “Blood alone moves the wheels of history. Stereotactic radiosurgery (SRS) moved the wheel of neurosurgery in the absence of bloodshed. Over the last five decades, SRS has made a phenomenal stride in the pursuit of being minimally invasive but equally effective. Though literature testifies for its effectiveness, feasibility, and applicability, the traditional mindset of a neurosurgeon feels it difficult to accept it open heartedly. Radiosurgery is essentially a neurosurgeon's tool with more partial, conservative, and pragmatic approach with sole intention to maintain lesion control while preserving the quality of life of the patient. It demands a thorough knowledge to be impregnated into young neurosurgeon's mind at the time of their training, else it would fascinate or frighten with biased opinions.